Pea dispersion as a basis for the production of fermented products - D. A. Samsonova; S. Barua; M. D. Gurda; N. V. Iakovchenko (Новые технологии, 2025)
Introduction. Plant-based products, including fermented products, are becoming increasingly popular. This is due to the fact that an increasing number of people adhere to vegetarianism for ethical, environmental, religious or medical reasons. The goal. The goal of the research was to determine the possibility of using pea dispersion as a basis for the production of fermented products with antioxidant properties. The Methods. The research was conducted in the laboratories of the Faculty of Biotechnology of ITMO University. The fermentation process of pea dispersion with Lactobacillus acidophilus, Lactobacillus delbrueckii subsp. shermani, Streptococcus thermophilus, Bacillus coagulans cultures was studied in terms of acid accumulation dynamics and changes in active acidity, biomass increase, changes in organoleptic properties after fermentation, as well as changes in antioxidant activity after fermentation and during storage. The Results. The fermentation efficiency of pea dispersion varies significantly depending on the culture used. The longest fermentation time of 15 hours was found in Bacillus coagulans strain, the shortest – 7 hours in Streptococcus thermophilus. Most samples showed an increase in biomass during fermentation of pea dispersion, with the highest values in samples fermented by B. bifidum - with an increase of 23.64% to 9.25 lg (CFU / ml) and B. coagulans MTCC 5856 - with an increase of 14.68% to 7.26 lg (CFU / ml). On the first day after fermentation, most samples showed an increase in antioxidant activity, which decreases during the shelf life. Fermentation leads to a significant improvement in the organoleptic properties of the product, improving homogeneity and reducing bitterness. Conclusion. Thus, pea dispersion is a promising basis for the production of both independent fermented products and as a fermented component of desserts, including frozen ones.